1999
DOI: 10.1037/0278-7393.25.2.464
|View full text |Cite
|
Sign up to set email alerts
|

Organizational factors in selective attention: The interplay of acoustic distinctiveness and auditory streaming in the irrelevant sound effect.

Abstract: A series of studies further explored the way in which irrelevant sound disrupts the serial recall of visually presented verbal sequences. The hypothesis that distinctiveness (stimulus mismatch) within auditory irrelevant sequences is a critical determinant of disruption of serial recall was tested. Experiment 1 showed that the degree of disruption was related to the degree of mismatch between successive stimuli. However, in Experiment 2, changes in 2 attributes of a stimulus produced less disruption than when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 34 publications
(57 reference statements)
5
101
0
Order By: Relevance
“…Of particular relevance is the finding by Jones, Alford, Bridges, and Macken (1999) that irrelevant sounds with segregated inharmonic components are less distracting than those with fused inharmonic components. The authors found that distractors containing tones deviant in both pitch and timbre were less distracting than those containing tones that deviated in either pitch or timbre.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Of particular relevance is the finding by Jones, Alford, Bridges, and Macken (1999) that irrelevant sounds with segregated inharmonic components are less distracting than those with fused inharmonic components. The authors found that distractors containing tones deviant in both pitch and timbre were less distracting than those containing tones that deviated in either pitch or timbre.…”
Section: Discussionmentioning
confidence: 96%
“…The authors found that distractors containing tones deviant in both pitch and timbre were less distracting than those containing tones that deviated in either pitch or timbre. Furthermore, the authors found that the former stimuli were no more distracting than a monotonous distractor that did not contain any tone deviants (Jones et al, 1999). Interpreting their results, the authors suggested, BPerhaps the key to understanding these contrary effects lies in an understanding of the modulating influence of auditory stream formation and its consequences for seriation,^(i.e., the encoding of a particular auditory stream), concluding in essence that when a tone is deviant in two parameters it is most easily streamed as a separate auditory object that does not interfere with the seriation of either the primary or distracting events.…”
Section: Discussionmentioning
confidence: 99%
“…This obligatorily and preattentively encoded order information is thought to conflict with the process of retaining the order of the to-be-remembered items. It is well established that for an auditory sequence to yield order cues, it must exhibit acoustic change between its constituent elements and, critically, these acoustic changes must constitute variations on a common ground (Bregman, 1990;Jones, Alford, Bridges, Tremblay, & Macken, 1999). That change on a common ground is a key principle in the irrelevant sound effect was first shown by Jones and Macken (1995a).…”
Section: Discussionmentioning
confidence: 99%
“…Repetition of a single sound disrupts performance less than a sequence of sounds in which each sound, if attended, would be perceived as a discrete entity differing from the one preceding it. Jones et al [31] and Macken et al [32] used ABA-ABA sequences as task-irrelevant background sounds. They varied either the frequency separation between the A and B tones or their presentation rate.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 99%